Simplified Methodology for the Evaluation of Geotechnical Vulnerability of Embankments on Mountain Roads in Costa Rica - Ulloa Calderón , Álvaro (2025)
This article presents a simplified evaluation method of the geotechnical vulnerability of road embankments on hill slopes that can be applied in risk management of mountainous roads. It is based on a theoretical stability analysis using different geometric configurations and geotechnical properties to simulate the most frequent conditions found in the mountainous routes of Costa Rica.  This investigation evaluates the stability of three models with different geometric, physical and geotechnical characteristics: "Varablanca", based on a real site and composed by two materials (foundation soil and fill), "infinite slope" and "Terrace embankment", composed by a single material type. The failure occurrence mechanisms in drained and undrained conditions were studied using the Bishop and modified Janbu methods and a computational software. The influence of parameters that affect stability was evaluated by changing the geometric configuration (height, width, angles of slopes, grading), geotechnical properties (water table level, humidity content, voids ratio, unit weight of materials, drained and undrained shear strength) and seismic coefficient.  As a general conclusion, the study confirms that failure occurs most frequently in undrained condition and it is caused by soil saturation. In drained condition, the maximum slope angle of the embankment is directly related to the friction angle of the material. In undrained condition, the maximum height of the embankment is directly related to the strength normalized by the unit weight of the material. These results show the importance of an adequate design, construction and maintenance of drainage structures to prevent damage or loss of the infrastructure.  The results of the study are presented in the form of equations and graphics that relate the stability safety factor with geometric, geotechnical and seismic characteristics. The use of the equations, which substitute detailed analysis for quick determination of the safety factor or the failure conditions, requires only the evaluation of material resistance parameters (φ' and c) and physical properties (ϒ), as well as the seismic coefficient (kh).  Five different real failure cases were analyzed in order to validate the use of simplified equations for the computation of the safety factor, the height of failure or the normalized strength. An overall error of less than 10% in all the parameters was obtained. In addition, the equations were used to propose preliminary evaluation criteria of the geotechnical vulnerability of slopes in mountainous roads. These are tools useful for risk management of mountainous roads.